The effect of location and type of nutrition content claims (NCCs) on healthy food purchase intentions: findings from an experimental study - Shouwei Li; Ping Liu; Yan Guo (BMC, 2020)
Abstract Background Nutrition Content Claims (NCCs) are often used to enhance the appeal of healthy food products. Appropriate horizontal positioning of different NCCs in the consumer's visual field may help to improve the effect of the claims. This study examines the extent to which NCCs on food packaging are effective depending on where the claims are located on the packaging and the type of claims. Methods Guided by the location effect, a 2 (claim type: benefit-seeking vs. risk-avoidance) × 2 (claim location: left vs. right) experiment is conducted to investigate the influence of NCCs located on the left side of the observer's visual field compared to claims on the right side of the observer's visual field on purchase intentions when the claim is either benefit-seeking or risk-avoidance. The study was conducted online. A total of 400 participants took part in the experiment. The study obtained valid data from 365 participants (44.11% males). Analyses examined the purchase intentions of food products with different claims located in different locations. Differences were tested using a general linear model, and a level of significance of 0.05 was used. Results The authors find that respondents show higher purchase intentions toward foods with risk-avoidance NCCs located on the left and toward foods with benefit-seeking NCCs located on the right side of the package. Conclusions The results provide implications and suggestions for improving healthy food packaging and marketing strategies and for public health policy.